Assessment of AQI, PM10, PM2.5, NO2, O3: The Case of Owo, Nigeria - Abulude, Francis Olawale; Akinnusotu, Akinyinka; Bello, Lateef; Feyisetan, Abigail Oluwakemi (ASEAN Journal of Science and Engineering, 2024)
When evaluating the quality of the air, the most important pollutants to keep an eye on are particulate matter (PM), NO2, CO, O3, and SO2 gases. Their impact on people and the environment is a simple fact. Before taking any action, it is necessary to determine how much of them are present in the air. Therefore, the purpose of this article is to evaluate the AQI, PM, and other pollutants present in the Nigerian town of Owo in Ondo State. This was accomplished with the help of the recently introduced AirVisual PM wireless sensor technology. It collects data on AQI, PM10, PM2.5, NO2, and O3 using satellite imagery. The AQI was interpreted using the Aculeated Air Quality Scale. The findings revealed that the AQI was in the average range. The NO2 values were lower than the advised limits when these findings were compared to WHO standards. While the O3 values were significantly below the 8-hour daily maximum and peak session, the PM values significantly exceeded the annual and 24-hour mean limits. Nigeria should start making efforts right away to stop activities that could increase pollution both inside and outside of the town of Owo, which is a rapidly expanding town in the Ondo State.